Increasing the Liquidus Temperature by Employing the Controlled Diffusion Solidification (CDS) Process: A Potential Route to Improved Castings. (May 2019) - Pourgharibshahi, Mohammad; Divandari, Mehdi; Saghafian, Hassan; Fabrizi, Alberto; Timelli, Giulio
Abstract: Recent theories suggest the existence of an incubation time, over which a liquid alloy prepares for nucleation by decomposing into compositional fluctuations. Accordingly, in a recent work by the present authors, the solidification path of a Controlled Diffusion Solidification (CDS) mixture was calculated. The calculated CDS path begins at a higher liquidus temperature comparing to conventional solidification and the fraction solid values are achieved at a relatively higher temperature. To provide information on the CDS mechanism and physical structure of the CDS mixture in the mushy zone, Al-7.8Zn-2.6Mg-2Cu alloy was solidified, in this study, via conventional and CDS process in the presence and absence of recalescence. Typical grain structures obtained via the two solidification conditions is characterized using Electron Back Scattered Diffraction. Results showed that the nucleation continues to occur in the presence of recalescence, while it is suppressed in its absence. According to the two step nucleation theory, the increase in the nucleation temperature causes sufficient recalescence in the mixture, allowing the unnucleated liquid phase to decompose into chemical fluctuations and prepares for further nucleation. As a result, in the presence of recalescence, nucleation in a CDS mixture is not as readily halted as during the conventional solidification, which is in contradiction with the recent theories developed based on the classical theory of nucleation.